Loss of SATB2 expression correlates with cytokeratin 7 and PD-L1 tumor cell positivity and aggressiveness in colorectal cancer - Hrudka, Jan; Matěj, Radoslav; Nikov, Andrej; Tomyak, Igor; Fišerová, Hana; Jelínková, Karolína; Waldauf, Petr (Scientific reports, 2022)
Colorectal carcinoma (CRC) is a disease that causes significant morbidity and mortality worldwide. To improve treatment, new biomarkers are needed to allow better patient risk stratification in terms of prognosis. This study aimed to clarify the prognostic significance of colonic-specific transcription factor special AT-rich sequence-binding protein 2 (SATB2), cytoskeletal protein cytokeratin 7 (CK7), and immune checkpoint molecule programmed death-ligand 1 (PD-L1). We analyzed a cohort of 285 patients with surgically treated CRC for quantitative associations among the three markers and five traditional prognostic indicators (i.e., tumor stage, histological grade, variant morphology, laterality, and mismatch-repair/MMR status). The results showed that loss of SATB2 expression had significant negative prognostic implications relative to overall survival (OS) and cancer-specific survival (CSS), significantly shortened 5 years OS and CSS and 10 years CSS in patients with CRC expressing CK7, and borderline insignificantly shortened OS in patients with PD-L1 + CRC. PD-L1 showed a significant negative impact in cases with strong expression (membranous staining in 50-100% of tumor cells). Loss of SATB2 was associated with CK7 expression, advanced tumor stage, mucinous or signet ring cell morphology, high grade, right-sided localization but was borderline insignificant relative to PD-L1 expression. CK7 expression was associated with high grade and SATB2 loss. Additionally, a separate analysis of 248 neoadjuvant therapy-naïve cases was performed with mostly similar results. The loss of SATB2 and CK7 expression were significant negative predictors in the multivariate analysis adjusted for associated parameters and patient age. In summary, loss of SATB2 expression and gain of CK7 and strong PD-L1 expression characterize an aggressive phenotype of CRC.
Keywords: Matrix Attachment Region Binding Proteins; prognóza; Colorectal Neoplasms; Prognosis; B7-H1 Antigen; antigeny CD274; kolorektální nádory; Biomarkers, Tumor; lidé; nádorové biomarkery; vazebné proteiny DNA v oblastech připojení k matrix; Keratin-7; transkripční faktory; keratin-7; Transcription Factors; Humans